Development and Validation of the Spanish Interval Scale of Anxiety Response (ISAR) - Heaton, Lisa J (American Dental Society of Anesthesiology, 2007)
As increasing attention is paid to disparities in oral health care, cross-cultural means for assessing dental fear, a significant barrier to dental care, are in high demand. There is, however, a surprising shortage of Spanish-language dental fear measures in the literature, despite evidence of dental fear and avoidance in Spanish-speaking populations. The goals of the current series of studies were to develop and validate a Spanish-language version of the Interval Scale of Anxiety Response (ISAR). Magnitude estimation, a technique in which participants are asked to assign a number to indicate the perceived intensity of a stimulus or phrase, was used to compare the Spanish ISAR to the original English ISAR during the development studies. As a result of the 4 initial development studies, modifications were made to both the Spanish and English scales. Once 2 seemingly equivalent scales were established, validation studies were completed with native Spanish- and English-speaking dental patients. The results suggest that both the Spanish and modified English ISAR scales are valid measures of state anxiety associated with dental treatment. Additionally, the results of these studies highlight the importance of thoroughly testing translated measures to ensure they are accurately assessing that which they purport to measure.